2005
DOI: 10.1007/s11199-005-4200-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Aggression in Marital Relationships: A Life-Span Perspective

Abstract: This study examines the relationship between age, gender, and marital aggression by comparing conflict resolution strategies, physical aggression, and injury across 6,185 married young, middle and older aged men and women. We found a consistent age effect such that younger participants used more maladaptive conflict resolution strategies, engaged in more physical arguments, and sustained more injuries than older participants. In terms of gender differences, women compared to men used calm discussions less (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 19 publications
5
51
1
2
Order By: Relevance
“…The results showed that duration of marriage was not correlated to marital adjustment. Finding of the study disagrees with the earlier finding of comparable research that indicated that duration of marriage is positively associated with marital satisfaction (e.g., Bali et al, 2010;Bookwala et al, 2005;Brown & Lin, 2012;Darvizeh & Kahaki, 2008). …”
Section: Discussion and Recommendationscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results showed that duration of marriage was not correlated to marital adjustment. Finding of the study disagrees with the earlier finding of comparable research that indicated that duration of marriage is positively associated with marital satisfaction (e.g., Bali et al, 2010;Bookwala et al, 2005;Brown & Lin, 2012;Darvizeh & Kahaki, 2008). …”
Section: Discussion and Recommendationscontrasting
confidence: 99%
“…Some research shows that the length of marriage is positively associated with marital satisfaction (Bookwala, Sobin, & Zdaniuk, 2005;Hatch & Bulcroft, 2004;Kulik, 2004). Research has shown that marital satisfaction is lower in long-term marriages than in those of short duration (Jansen et al, 2006).…”
Section: Duration Of Marriage and Adjustmentmentioning
confidence: 99%
“…Specific to domestic relationships, however, researchers have found that men and women use aggression with similar frequency (e.g., Bookwala, Sobin, & Zdaniuk, 2005). However, Bookwala et al reported that the injuries inflicted by violence differed for men and women, with men inflicting more severe injuries and being more likely to kill their partner (see also Hamby, 2005).…”
Section: Hands-on Killingmentioning
confidence: 99%
“…Using cross-sectional data from the National Family Violence Surveys, Suitor, Pillemer, & Straus (1990) found that couple physical aggression does decrease with age from adolescence to late adulthood and concluded that this reduction is not merely an artifact of generation or cohort differences. In the National Survey of Families and Households, Bookwala, Sobin, and Zdaniuk (2005) found that male and female physical aggression was lower with each increasing age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and 60+ year olds), but males and females had similar rates of aggression within each of the three age groups.…”
Section: Partner Aggression Over the Life Coursementioning
confidence: 99%